OUTH LANGUAGE AND SOCIAL STRATIFICATION: THE ROLE OF SLANG IN SOCIAL IDENTITY FORMATION - Otajonov Umidjon, Abduvokhidov Javohir Abduvohidovich, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Slang is an important element of youth language and social stratification, playing a major role in defining social identity and group affiliation. This article analyzes how slang affects social stratification, linguistic innovation, and communication dynamics among young people. It also focuses on aspects of slang such as creating differences between social groups, its use as linguistic capital, and its dissemination through modern technologies. The article also examines the changing nature of slang and its impact on language and social relations.